PERAN STRES KERJA MEMEDIASI BEBAN KERJA TERHADAP SEMANGAT KERJA PERAWAT RUMAH SAKIT WANGAYA SAAT COVID-19 - Paramitha, Desak Putu Chinintya; Rahyuda, Agoes Ganesha (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.03.TAHUN.2023DO - 10.24843/EEB.2023.v12.i03.p02, 2023)
This study aims to analyze the role of work stress in mediating the effect of work on the work of nurses at Wangaya Hospital during the Covid-19 period. The research location is Wangaya Hospital in Denpasar City. The sample obtained is 138 people who are determined by proportional random sampling technique. Data collection was carried out using a survey approach and approach. Data analysis was carried out using PLS-based SEM, namely Smart Pls. The results showed that workload had a significant negative effect on work morale, workload had a significant positive effect on work stress and stress had a significant negative effect on work morale. Another finding is that work stress is not a mediator of the relationship between workload and the morale of nurses at Wangaya Hospital Denpasar. Practically, the findings of this study can be used by hospital managers to maintain the work of nurses through the provision of work morale in accordance with abilities and regulations. In addition, hospital managers should avoid making policies that can create work stress by testing new rules.